2004
DOI: 10.1364/ao.43.003061
|View full text |Cite
|
Sign up to set email alerts
|

High-order correlations from rough-surface scattering

Abstract: It is proposed to apply an optical setup of a randomly weak rough dielectric film on a reflecting metal substrate for the measurement of high-order correlations from rough-surface scattering. The angular amplitude and intensity correlations are measured. Because of multiple scattering, when the input laser beam size is comparatively small or close to the travel pass length inside the film, C(2) and C(3) are measured by subtraction of the amplitude correlation from the intensity correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Laser speckle analysis has been used in the past as a surface roughness characterization technique [23][24][25] , and it was found that different scattering processes give rise to distinct speckle correlation lengths. Multiple scattering processes can be differentiated from single or weak scattering processes through the intensity or field statistics 18,19 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Laser speckle analysis has been used in the past as a surface roughness characterization technique [23][24][25] , and it was found that different scattering processes give rise to distinct speckle correlation lengths. Multiple scattering processes can be differentiated from single or weak scattering processes through the intensity or field statistics 18,19 .…”
Section: Resultsmentioning
confidence: 99%
“…Near the MIT transition temperature, a secondary peak develops away from the central maximum region, as seen most prominently in Fig 4(a) and (b) at T = 57 °C for an illumination wavelength 633 nm and at a slightly higher temperature of 59 °C for 800 nm. The secondary maxima are a signature of long range correlation, which indicates a decreased scattering mean free path 25 and increased scattering strength. Additional small maxima at different positions are also noticeable at temperatures 61 °C for 800 nm and 62 °C for 633 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation